The Effect of Boron Nitride Nanocage on the Thermodynamic and Energetic Properties of TATB - S. Sepehr Uroomiye; Neda Hajizadeh; Helen Aazh (International Journal of New Chemistry, 2020)
In this research, IR and frontier molecular orbital computations were employed for investigating the influence of B12N12 on the energetic and thermodynamic parameters of TATB. The Computed enthalpy changes and Gibbs free energy variations showed TATB interaction with this nanostructure is exothermic, spontaneous, and experimentally possible. The specific heat capacity values (CV) revealed the heat sensitivity of TATB has improved sharply after its interaction with BN nanocage. Some structural features like bandgap, chemical hardness, chemical potential, electrophilicity, and maximum transferred charge capacity were also computed and the results indicated that the reactivity, conductance, and electrophilicity of TATB enhances substantially after its reaction with B12N12. All of the computations were done by density functional theory in the B3LYP/6-31G(d) level of theory.